When business met politics: the case of Want Want, a different type of media capital in Taiwan - Lin, Lihyun; Lee, Chun-Yi (Centre d'étude français sur la Chine contemporaine, 2017)
Since 2008, the Taiwanese business group Want Want, having made a fortune in China, has returned to Taiwan to buy a major media group and attempt to exert political influence on Taiwanese society. This paper analyses the rise and rationale of this new type of media investor in the light of the business/government relationship under China’s model of state capitalism. According to the analysis developed in this paper, when China needed foreign investment in the early 1990s, Taiwanese investors were warmly welcomed by the Chinese government, which provided Taiwanese businesses with tax incentives at that time. After 2000, however, when not only domestic Chinese entrepreneurs emerged but also more non-Chinese investors entered the Chinese markets, Taiwanese businesses realised that the investment environment had become much more competitive, so they had to work hard on building ties with Chinese officials. Under these circumstances, Want Want bought into media in Taiwan as an asset to be used in order to build social ties with the Chinese government, but in doing so, Want Want has also triggered resistance from Taiwanese civil society. Future researchers and regulators can continue to watch and define this new type of investment, which has become increasingly significant in this region.